Effects of xanthan gum on the rheological, physical and sensory prophets of purple sweet potato-wheat bread. - Tengco, Ralph Jason L.
This study aimed at determining the rheological, physical and sensory properties of the purple sweet potato-wheat bread by the addition of xanthan gum. Xanthan gum has been reported to improve dough handling properties, loaf specific volume, and crumb softness when incorporated into composite cassava-wheat bread formulations. However, there seems to have dearth of information on the application of xantham gum on the purple sweet potato-wheat formulations. Xantham gum in various concentrations (0.15% w/w, 0.30% w/w and 0.50% w/w) were added into bread formulation and the effects were observed by sensory and physico-chemical analyses. Results of Kramer?s Rank Sum test for preference revealed that the addition of xanthan gum at 0.30% was the Most Preferred Formulation (MPF). Dough viscosity, bread specific volume, mean cell area, moisture content and total sugar were determined and compared to contrl using Two-sample T-test. Evaluation of the different sensory attributes was done using Mann-Whitney Test. The addition of xanthan gum resulted in significantly higer (P<0.05) dough viscosity, specific volume, mean cell area, moisture and total carbohydrates content of the MPF when compared to control. For the sensory evaluation, no significant differences were observed in the crust color, degree of sweetness and presence or absence of PSP flavor. However, significant differences (P<0.05) existed in mouthfeel and texture between the control and MPF. The MPF recorded a higher rating of like very much than the control, with a like moderately rating in general acceptability. Addition of xanthan gum at 0.30% (w/w) concentration in the purple sweet potato-wheat bread formulation improved the physical, rheological and sensory properties of the bread, as well as its chemical composition, and the overall acceptability of the product.